BRIDGING THE GREEN GAP: DOES AUDIT COMMITTEE EFFECTIVENESS MODERATE THE IMPACT OF CARBON EMISSION DISCLOSURE ON FIRM VALUE? - Tita Nurvita; Maria Evy Purwitasari (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2026)
This study aims to analyze the effect of carbon disclosure on firm value, moderated by the role of the audit committee. The sample consists of energy sector issuers listed on the Indonesia Stock Exchange. The sampling period is 2021–2023. The sampling method used is purposive sampling. Data was obtained from idx.co.id and ESGI. The dependent variable in this study is firm value (FV), proxied by TobbinsQ; the independent variable is carbon disclosure (CED). The control variables are ROA and DER. The moderating variable is the audit committee (AC), proxied by the number of meetings attended by the Audit Committee Chair. Data was analyzed using OLS multiple regression. Model 1 shows that CED has a significant positive effect on firm value with a p-value of 0.04 < 0.05. The same was found for both ROA and DER, where there was a negative effect on firm value with p-values of 0.00 and 0.004, respectively. Model 2 shows that the audit committee fails to moderate the relationship between CED and firm value.Keywords: audit committee, firm value, carbon emission disclosure, carbon, sustainability reporting